Non-urgent users in a safe handling unit: prevalence of depressive symptoms (Research, Society and Development, 2020)
To identify the frequency of depressive symptoms in patients characterized as non - urgent attended at the emergency room of the Regional Hospital of Guaraí - TO - Brazil. Descriptive study with random probabilistic sample, considering a frequency of non-urgent queries of 80% with an acceptable error of 5%, the estimated sample size was 198 for the 95% confidence level and with a delineation effect of 1.0. Questionnaires were applied to patients classified as non-urgent. We used variables such as age, gender, marital status, health care service and CES-D instrument to track depressive symptoms. Descriptive statistics were performed, with analysis of mean, standard deviation for continuous variables and percentage for categorical variables. The study found that 93 female patients presented depressive symptoms, while the male patients counted 54 cases attended at the Emergency Unit. The prevalence of young people with depressive symptoms was 63 cases, while adults accounted for 45 and the elderly 39. The incidence of people with no partner with depression occurred in 87 of the cases, however, among the patients with a partner counted 60 occurrences. The occurrence of patients with the presence of depressive symptoms occurred in 89 cases that were not urgent, while the prevalence of non-urgent cases was 58 of the cases attended by the Emergency Unit. Considering the correlation between the search for non-urgent care in secondary care and depression, it is necessary to plan strategies to enable the process of identification and early diagnosis of patients depressive.